1975
DOI: 10.1007/bf00447326
|View full text |Cite
|
Sign up to set email alerts
|

Halobacterium volcanii spec. nov., a Dead Sea halobacterium with a moderate salt requirement

Abstract: A halophilic bacterium was isolated from bottom sediment from the Dead Sea. The organism possessed the properties of the halobacteria, but differed from the known species in two important respects, 1) the cells were disc shaped and often cupped when grown under optimum conditions, 2) the optimum requirements for sodium chloride was in the range 1.7--2.5 molar which is about half of that generally reported for the halobacteria. The organism was assigned to the genus Halobacterium and described as Halobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
235
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(247 citation statements)
references
References 11 publications
9
235
0
3
Order By: Relevance
“…In the original report of the strain, it was shown that disruption of the plasma membrane by osmotic lysis upon transfer of cells into water yielded small, sealed membrane vesicles [32]. Unfortunately, the topological orientation and preservation of membrane protein function in these vesicles was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…In the original report of the strain, it was shown that disruption of the plasma membrane by osmotic lysis upon transfer of cells into water yielded small, sealed membrane vesicles [32]. Unfortunately, the topological orientation and preservation of membrane protein function in these vesicles was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…The natural adaption of proteins to halophilic habitats poses significant challenges, and proteins may express inactive or form inclusion bodies. Refolding procedures may restore enzyme activity (Connaris et al 1998a ;Mullakhanbhai and Larsen 1975 ), but this method is not general, and many enzymes remain inactive (Timpson et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…A typical example is the application of the archaea Haloferax volcanii, which was isolated from the Dead Sea by Benjamin Volcani in the 1940s (22). For optimal growth, it requires 2.6 M NaCl and a temperature between 42 and 45 °C (Mullakhanbhai and Larsen 1975 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two such events have been documented: in 1980, and even more dramatically in 1992, when the upper 5 m of the water column was diluted up to 70%, supporting a density of Archaea up to 3.5 Â 10 7 ml -1 , coloring the Dead Sea water red . A number of species of halophilic Archaea have been isolated from the Dead Sea, including Haloferax volcanii (Mullakhanbhai and Larsen, 1975), Haloarcula marismortui (Oren et al, 1990), Halorubrum sodomense (Oren, 1983) and Halobaculum gomorrense . However, polar lipid analyses of biomass collected during Dead Sea blooms suggested that these isolates were not the major components of the microbial community at the time (Oren and Gurevich, 1993).…”
Section: Introductionmentioning
confidence: 99%